Risk assessment and acute toxicological effects of atrazine on Nile tilapia larvae after stress. Issue 1 (15th October 2020) - Chiste, Bruna Milke; Takeshita, Natalia Akemi; Mattioli, Cristiano Campos; Jonsson, Claudio Martin; Barizon, Robson Monticelli; Hisano, Hamilton
Abstract: The present study aimed to evaluate the risk assessment, median lethal concentration LC50-96h, development, and mortality of Nile tilapia Oreochromis niloticus larvae exposed to atrazine after stress management. An LC50-96h trial was carried out using fish (n = 147; 8.5 ± 1.0 mg; seven larvae/aquarium), which were allocated randomly in 21 aquaria (1 L) and exposed to five concentrations of atrazine: 2, 4, 8, 16, and 32 mg L −1 plus one control (without herbicide) and a control with a solubility adjuvant (acetone). Temperature, pH, dissolved oxygen, conductivity, and total ammonia were measured daily. In addition, a stress test was performed with fish (n = 150; 17.9 ± 1.7 mg; 10 larvae/aquarium) submitted to air exposition (five minutes) and posteriorly distributed randomly in 15 aquaria (1 L), and exposed to atrazine at 0.18, 6, 12, and 18 mg L −1 . The LC50-96h of atrazine for Nile tilapia larvae was 17.87 mg L −1 . Significant differences ( P  < 0.05) were found for weight and final length, pH, and dissolved oxygen that was responsive to the increased levels of herbicide. Larvae mortality post-stress was registered to 6, 12, and 18 mg L −1 of atrazine, and was more critical at 24 h. The increased doses of atrazine used in LC50-96h test depressed the development of Nile tilapia larvae. Fish submitted to stress (air exposition) and exposed to sub-lethal doses of atrazine showed significant mortality, indicating that stressors may increase the toxic effect of atrazine for Nile tilapia larvae. On the other hand, based on risk assessment atrazine can be classified as herbicide with low toxicity for Nile tilapia larvae and low toxicological risk.